Functional data analysis of running kinematics in chronic achilles tendon injury - Donoghue, O. A.; Harrison, A. J.; Coffey, N.; Hayes, K. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Chronic Achilles tendon (AT) injuries are common, but kinematic studies confirming the exact mechanisms of injury and how orthoses are effective are lacking. Existing analysis often relies on discrete measures and provides an incomplete analysis because many of the data are discarded. Functional data analysis (FDA) views the entire dataset as a function, thus retaining the main features of the curve. This study uses FDA to examine the mechanisms of chronic AT injury and the functional effects of orthoses.